Gold‐Catalyzed Synthesis of 1‐Naphthylcarbenoids and Their Synthetic Utilization in Cyclopropanation Reactions. Issue 4 (3rd March 2014) - Lauterbach, Tobias; Ganschow, Michael; Hussong, Matthias W.; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K.
Abstract 1‐Naphthylcarbenoids are generated via 1, 2‐acyl migration and subsequent carbene shift from simple, easily available diyne starting materials. These highly reactive species were allowed to react with differently substituted alkenes in both intermolecular and intramolecular fashions. In the intermolecular cases even a simple 1:1 ratio of the starting materials delivered the corresponding cyclopropylnaphthalenes in high yields by the use of a gold(III) catalyst. The methodology offers a completely new approach to these valuable targets, the new route represents an efficient alternative to common methods that are based on cross‐coupling strategies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>